Methoxy poly(ethylene glycol)-b-poly(ε-caprolactone) block-graft copolymers with pendant fluorescent groups: synthesis, characterization and cellular uptake - Peng, Kang-Yu; Wang, Shiu-Wei; Hua, Mu-Yi; Lee, Ren-Shen (Journal of polymer research, 2013)
Block-graft methoxy poly(ethylene glycol)- b -poly(ε-caprolactone) copolymers with pendant fluorescent pyrene groups were synthesized by post-polymerization conjugation of 1-pyrenemethyl 4-pentynoate (PMP) onto azido-functionalized MPEG- b -PαN 3 CL using the “click” reaction. Copolymers were characterized by differential scanning calorimetry (DSC), 1 H NMR, IR, and gel permeation chromatography. The block-graft copolymers formed micelles in the aqueous phase, with critical micelle concentrations (CMCs) in the range of 2.9–19.4 mg L −1 . Transmission electron microscopy (TEM) was used to analyze micelle morphology, and it revealed a spherical structure. The mean hydrodynamic diameters of the micelles from dynamic light scattering were in the range of 38–96 nm. In vitro cell viability assay indicated that MPEG- b -(PαN 3 CL- g -PMP/alkyne) has low cytotoxicity. Doxorubicin hydrochloride (DOX)-loaded micelles facilitated human cervical cancer (HeLa) cell uptake of DOX; uptake was completed within 4 h, and DOX was able to reach intracellular compartments and enter nuclei by endocytosis. Figure DOX-loaded MPEG 45 - b -(PαNCL 26 - g -PMP 7 /Hexy 19 ) micelles (13) provide greater uptake of DOX by HeLa cells compared to the non-encapsulated drug (A), and were able to enter nuclei by endocytosis (C).